Aanalisis Perbatasan Laut Antara Peru dan Chili Yang Di Selesaikan Oleh Mahkamah Internasional - Widia Wiliani Sipayung (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This study describes the efforts made on the maritime boundary issues that occurred between Peru and Chile. Each began in 1947, where the State claimed jurisdiction and exclusive rights to waters 200 miles from each other's coast. The official dispute that occurred between the two began in 2007 when Peru certified the description of the sea that overlapped between the two parties. This type of research is qualitative. The research method used is descriptive analysis technique. Most of the data was collected through library studies and website searches. The data obtained were then analyzed using a theoretical approach related to International Relations, namely international organizations. The results of the study show that from both countries there were no results that described peace over the dispute that occurred because both countries had different interpretations of the borders they had. The last effort was taken firmly by Peru where the dispute would be submitted to the International Court of Justice in order to obtain peace and a decision on the sea areas of Peru and Chile in accordance with International Law through the International Court of Justice (ICJ).